Álbum fotográfico sobre cuerpos parlantes disidentes en un mundo binario. - Larrea Cabrera, María del Cisne (2016)
We are energies, essences bodies and not the representation of a reductionist view of what should be a man / woman while conditional and configure their attitudes, forms of communication and social roles. In this paper what is intended is to show how some people have been breaking the conventions, giving a totally valid and broad meaning to the sense of diversity. Breaking with the idea of naturalizing gender, event in which the name ascribed to sexual differences that human being and to the practices that have as a starting point our sexuality and our control over this is evident. Shelve gender conventions and accept that bodies are no longer man or woman to pass recognized as "talking bodies." Show as the identity of several individuals from the society is composed of the fluid mix and the incorporation of attributes of both genders, breaking labels and diagrams already imposed.